ECOLOGICAL DISCOURSE AND THE DEVELOPMENT OF CRITICAL LITERACY IN EFL EDUCATION - Sadullayeva Zukhra Murodullayevna (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: This article examines the role of ecological discourse in developing critical literacy within EFL education. It highlights the relationship between discourse interpretation, ecological awareness, and critical engagement with sustainability-related communication in foreign language learning. The study emphasizes that ecological discourse encourages learners to critically analyze ideological assumptions, environmental narratives, and socially significant representations embedded in communication. The findings demonstrate that integrating ecological discourse into EFL education contributes not only to language development, but also to the formation of critical literacy, reflective thinking, and socially responsible communication among learners.